Tinjauan Yuridis terhadap Perlindungan Nasabah Perbankan Yang Menggunakan Layanan Internet Banking - Indriana Syiffa Fauziah; Rani Apriani (Universitas Batanghari Jambi, 2021)
Nowadays technology is experiencing very rapid development, especially in conducting transactions and communication, namely by utilizing the internet as a medium, one of which is banking that uses the role of the internet or also called internet banking. The purpose of this study is to find out how the security of banking information is to uphold the principle of confidentiality in protecting the identity of customers who useproducts or services Internet banking, legal protection against the use of Internet banking, and the responsibility of banks to customers who suffer losses due to the use of internet banking. The research method used is normative juridical with analytical descriptive approach, through qualitative analysis techniques and data collection techniques through literature study using secondary data derived from primary legal materials, secondary legal materials and tertiary legal materials. From the results of this study found that the security protection of banking information by implementing a mechanism that has the purpose to avoid the various cybercrime or adverse impact on the security or confidentiality of customer informationusers, internet bankinglegal protections, regulated in Law Number 10 of 1998 concerning Banking and Law Number 11 of 2008 which was amended to Law Number 19 of 2016 concerning Electronic Information and Transactions, Law Number 8 of 1999 concerning Consumer Protection, Law Number 36 of 1999 concerning Telecommunications and Electronic Transactions, as well as in In terms of responsibility, the bank provides compensation as agreed with the customer through prior checking.